Strengthening Employability Skills Programme and IEM's AFETD membership drive - Samsuzana, Abd. Aziz, Engr. Dr.; Hasfalina, Che Man, Engr. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.